Novel genetic variants in MAPT and alterations in tau phosphorylation in amyotrophic lateral sclerosis post‐mortem motor cortex and cerebrospinal fluid. (14th November 2021) - Petrozziello, Tiziana; Amaral, Ana C.; Dujardin, Simon; Farhan, Sali M. K.; Chan, James; Trombetta, Bianca A.; Kivisäkk, Pia; Mills, Alexandra N.; Bordt, Evan A.; Kim, Spencer E.; Dooley, Patrick M.; Commins, Caitlin; et al.
Abstract: Although the molecular mechanisms underlying amyotrophic lateral sclerosis (ALS) are not yet fully understood, several studies report alterations in tau phosphorylation in both sporadic and familial ALS. Recently, we have demonstrated that phosphorylated tau at S396 (pTau‐S396) is mislocalized to synapses in ALS motor cortex (mCTX) and contributes to mitochondrial dysfunction. Here, we demonstrate that while there was no overall increase in total tau, pTau‐S396, and pTau‐S404 in ALS post‐mortem mCTX, total tau and pTau‐S396 were increased in C9ORF7 2‐ALS. Additionally, there was a significant decrease in pTau‐T181 in ALS mCTX compared controls. Furthermore, we leveraged the ALS Knowledge Portal and Project MinE data sets and identified ALS‐specific genetic variants across MAPT, the gene encoding tau. Lastly, assessment of cerebrospinal fluid (CSF) samples revealed a significant increase in total tau levels in bulbar‐onset ALS together with a decrease in CSF pTau‐T181:tau ratio in all ALS samples, as reported previously. While increases in CSF tau levels correlated with a faster disease progression as measured by the revised ALS functional rating scale (ALSFRS‐R), decreases in CSF pTau‐T181:tau ratio correlated with a slower disease progression, suggesting that CSF total tau and pTau‐T181 ratio may serve as biomarkers of disease in ALS. Our findings highlight the potential role of pTau‐T181 in ALS, as decreases in CSF pTau‐T181:tau ratio may reflect the significant decrease in pTau‐T181 in post‐mortem mCTX. Taken together, these results indicate that tau phosphorylation is altered in ALS post‐mortem mCTX as well as in CSF and, importantly, the newly described pathogenic or likely pathogenic variants identified in MAPT in this study are adjacent to T181 and S396 phosphorylation sites further highlighting the potential role of these tau functional domains in ALS. Abstract : Although the molecular mechanisms underlying amyotrophic lateral sclerosis (ALS) are not yet fully understood, recent studies report alterations in tau phosphorylation in ALS. Our study builds on these findings and demonstrates that tau phosphorylation is altered in post‐mortem ALS motor cortex and highlights new and ALS‐specific variants in MAPT, the gene encoding tau. Lastly, we report alterations in phosphorylated tau in ALS cerebrospinal fluid that may function as a predictive biomarker for ALS.